Numerical investigation of graphene derivatives as HTL in PBDB-T:NCBDT bulk heterojunction organic solar cell - Denet Davis; K.S. Sudheer (Results in Optics)
The damaging effects of the most widely used PEDOT:PSS have led researchers to search for an alternative hole transport layer (HTL) in non-fullerene acceptor (NFA) based bulk heterojunction organic solar cells (BHJOSC’s). This work highlights the numerical simulation study of possible new approach of utilizing graphene, graphene oxide (GO), reduced graphene oxide (rGO), and p type doped graphene (p-graphene), as an alternative to PEDOT:PSS in non-fullerene acceptor based bulk heterojunction organic solar cell (NFABHJOSC) with PBDB-T as donor and NCBDT as acceptor using SCAPS1D. NCBDT is an emerging small-molecule non-fullerene acceptor (SM-NFA) whose bandgap can be tuned and reduced, making it a better option as an acceptor. Validation of the software is done by matching simulation results with experimental results. Diverse electron transport layers (ETL’s), including PDINO, ZnO, IGZO, TiO2, TiO2:gr (20%) composite, and TiO2:gr (10%) composite, are introduced, and device performance of various configurations is analysed. Optimization of the best device configuration ITO (4.8 eV)/rGO/PBDB-T:NCBDT/PDINO/Al gave an improved efficiency of 17.47%, fill factor (FF) of 77.45%, short circuit current density (Jsc) of 25.407 mA/cm2, and an open circuit voltage (Voc) of 0.8878 V.